Measuring environmental concern of Urban Green Spaces’ Users (UGSU) through the application of the New Ecological Paradigm Scale (NEPS): evidence from a southern european city - Vidal, Diogo Guedes (2021)
The New Ecological Paradigm scale (NEPS) is a worldwide survey-based metric, designed to measure the environmental concern of groups of people through a single instrument including fifteen statements. As far as it is known, the NEPS has never been previously applied to Urban Green Spaces’ Users (UGSU). The assessment and analysis of this group’s perception of the environmental concern could be a core element in promoting environmental sustainability. This research aims to measure and analyse UGSU (n = 132) NEPS score in a southern European city. The factor structure and psychometric properties of the NEPS revealed good internal consistency and the explained variance is higher than the original study. Thus, its application is considered reliable when applied to UGSU. UGSU presented higher ecocentric values when compared to the general population, university teachers and agricultural farmers. Concerning UGSU sociodemographic characteristics, the youngers adults are those that mostly share an ecological worldview. Also, those that more often visit Urban Green Spaces (UGS), recognized that plants and animals have the same right to exist as humans. It is expected that this work may contribute to explore the usefulness of the NEPS application in different contexts and to underline values that will have a significant effect on debates involving environmental sustainability as a cross-cutting issue.